IMPROVING STUDENTS’ SPATIAL IMAGINATION THROUGH TEACHING CREATIVE THINKING (in drawing classes) - Yakubova Nafisa Odiljanovna (International Scientific and Current Research Conferences, 2025)
In the first way of developing spatial imagination, the spatial imagination of students is increased by using drawings given on objects, mentally dividing them into simple figures and drawing up their clear image. Indeed, if there is a clear image of the object depicted in the figure, it becomes easier for the student to visualize the object, the appearance of which is given in the figures.